Kajian Systematic Literature Review (SLR) Untuk Mengidentifikasi Dampak Terorisme, Layanan Konseling dan Terapi Trauma Pada Anak-Anak - Urotul Aliyah; Mulawarman Mulawarman (Islamic Counseling : Jurnal Bimbingan dan Konseling Islam, 2020)
The purpose of writing this article is to determine the impact of terrorism on children and adolescents who live in the area of terror. The method used is the method of systematic literature review (SLR). SLR is a method that identifies, evaluates, and interprets findings on a research topic to answer a predetermined research question. From planning, conducting and reporting it can be concluded that terrorism has had a traumatic impact on many people, especially children and adolescents. The impact of terrorism can be experienced by children and adolescents in those who live at the scene of terror and children and adolescents of families of terrorists who experience negative stigma from the community as a family of terrorists. Children and adolescents affected by terrorism experience crucial problems to be able to rise up and undergo their psychological development naturally and without the pressure of trauma so that they need certain counseling so that they get up and are optimistic about their life's journey and the next stages of development. The recommendation of this study is the need for counseling to take on the role of strategy as an effort to build positive attitudes of children in facing the next stage of life so that they can undergo and realize career development positively as is usual for children and other adolescents who are not affected by terrorism. Moreover, learning from many countries, the government as a state representative must continue to be encouraged to care and dare to build a strong willingness to form institutions and regulatory frameworks for counseling services in many fields for increasingly diverse needs, especially the handling and prevention of trauma from the impact of terrorism.